Great Britain. Parliament. House of Commons records - Great Britain. Parliament. House of Commons
Unofficial journals (4 volumes, 1627-1687) of proceedings kept by or for Lord Lonsdale; volume relating to Court of Commons; and volume relating to commissioners of the House of Commons.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Lonsdale, John Lowther, -- Viscount, -- 1655-1700.; Great Britain. -- Parliament. -- House of Commons. -- Court of Commons; Great Britain -- History -- Stuarts, 1603-1714.; Great Britain -- Politics and government -- 1603-1714.